Moral Hazard Testing (Risk Transfer Behavior) in the Deposit Insurance System Based on Fair Premium for Determining Coverage Limit - Firman Pribadi, Eduardus Tandelilin, Suad Husnan, Manduh M. Hanafi (FEB Publication Office, 2015)
This research tries to answer a problem that commonly rises in the Deposit Insurance system which is still new, the right value of coverage limit for the Deposit Insurance system in Indonesia. The coverage limit which is too high will encourage moral hazard from the IDIC banks to the IDIC, while the coverage limit which is too low can affect the stability of the financial system of a country. The results of the study show that the coverage limit of IDR 100 million per account and 1 billion per account indicates the occurrence of moral hazard from the banks of the IDIC to the IDIC. However, the results also show that the encouragement toward moral hazard behavior from the banks of the IDIC to the IDIC is not too big when the coverage limit is up to IDR 100 million per account. Thus, the results and the model of this research can be used as a consideration by the Deposit Insurance agency (LPS) in determining the optimal coverage limit